Validated determination method of tramadol and its desmethylates in human plasma using an isocratic LC-MS/MS and its clinical application to patients with cancer pain or non-cancer pain. Issue 1 (December 2016) - Tanaka, Hironari; Naito, Takafumi; Mino, Yasuaki; Kawakami, Junichi
Abstract Background This study aimed to develop a simultaneous determination method for tramadol and its desmethylates in human plasma using isocratic liquid chromatography coupled to tandem mass spectrometry and to validate it for pharmacokinetic evaluation in patients with cancer pain or non-cancer pain. Methods The pretreatments for human plasma involved protein precipitation using acetonitrile and methanol under basic conditions. Tramadol, O -desmethylate, N -desmethylate, andN, O -didesmethylate were separated on an octadecylsilyl column filled with 3-μm particles using isocratic mixture of methanol and 0.15 % formic acid in water (35:65, v/v). The mass spectrometer was run in positive ion multiple reaction monitoring mode. This method was applied to the determination of plasma samples in patients treated with oral tramadol. Results The chromatographic total run time was 10 min. The calibration curves in human plasma of tramadol, O -desmethylate, N -desmethylate, andN, O -didesmethylate were linear over the concentration ranges of 12.5–1600, 2.5–320, 2.5–320, and 2.5–320 ng/mL, respectively. The lower limits of quantitation of tramadol and its desmethylates in human plasma were 12.5 and 2.5 ng/mL. Their extraction recoveries were 85.5–106.3 %. The intra-day and inter-day precisions and accuracies were 1.6–10.2 % and 89.2–106.2 % for all analytes. The plasma concentration ranges of tramadol, O -desmethylate, N -desmethylate, andN, O -didesmethylate were 18.2–564, 11.8–137, 4.9–250, and 6.1–147 ng/mL in cancer patients, and 32.8–670, 7.0–84.8, 5.1–317, and 6.7–85.2 ng/mL, respectively, in non-cancer patients. Conclusions The present method with acceptable analytical performance can be helpful for evaluating the pharmacokinetics of oral tramadol, including the determination of its desmethylates, for patients with cancer pain or non-cancer pain in clinical settings.